Pengaruh Pemberian Kredit Usaha Rakyat Terhadap Pendapatan Umkm Di Kota Pariaman Pasca Covid 19 - Zaki Zaki (CV. ITTC INDONESIA, 2022)
This study aims to determine the effect of providing people's business loans on the income of MSMEs in Pariaman City after the Covid 19 Pandemic. This title is based on the economic phenomenon that has occurred in recent years, the occurrence of covid-19 is the main factor for MSME actors to borrow KUR to increase business capital. , where we know the lowest KUR interest rate compared to other loan models. This research uses quantitative research. Data taken by distributing questionnaires to MSME actors who received KUR financing in Pariaman City after covid 19. With the results of the study, it was stated that the results of the tests that have been carried out prove that the provision of People's Business Credit has a significant effect on the income of MSMEs in Pariaman City after the Covid 19 Pandemic, and it can also be seen that the R Square value is 0.378 or 37.8%. This means that the Effect of Public Business Credit Provision of 37.8% on MSME Income in Pariaman City after the Covid 19 Pandemic. The remaining 62.2% is influenced by other variables outside of the this research variable.